Cryptic diversity and multiple origins of the widespread mayfly species group Baetis rhodani (Ephemeroptera: Baetidae) on northwestern Mediterranean islands. Issue 21 (11th October 2016) - Bisconti, Roberta; Canestrelli, Daniele; Tenchini, Roberta; Belfiore, Carlo; Buffagni, Andrea; Nascetti, Giuseppe
Abstract: How the often highly endemic biodiversity of islands originated has been debated for decades, and it remains a fervid research ground. Here, using mitochondrial and nuclear gene sequence analyses, we investigate the diversity, phylogenetic relationships, and evolutionary history of the mayfly Baetis gr. rhodani on the three largest northwestern Mediterranean islands (Sardinia, Corsica, Elba). We identify three distinct, largely co‐distributed, and deeply differentiated lineages, with divergences tentatively dated back to the Eocene–Oligocene transition. Bayesian population structure analyses reveal a lack of gene exchange between them, even at sites where they are syntopic, indicating that these lineages belong to three putative species. Their phylogenetic relationships with continental relatives, together with the dating estimates, support a role for three processes contributing to this diversity: (1) vicariance, primed by microplate disjunction and oceanic transgression; (2) dispersal from the continent; and (3) speciation within the island group. Thus, our results do not point toward a prevailing role for any of the previously invoked processes. Rather, they suggest that a variety of processes equally contributed to shape the diverse and endemic biota of this group of islands. Abstract : How the highly endemic biodiversity of islands originated has been debated for decades, and it remains a fervid research ground. Here, we investigate the diversity and evolutionary history of the mayfly Baetis gr. rhodani on the northwestern Mediterranean islands. We identify three distinct, largely co‐distributed, and deeply differentiated lineages, likely belonging to three putative species. Our results suggest that this diversity has been shaped by a variety of equally contributing evolutionary processes, including the following: (1) vicariance, primed by microplate disjunction and oceanic transgression; (2) dispersal from the continent; and (3) speciation within the island group.